2009
DOI: 10.1055/s-0031-1278354
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis causing lower extremity deep vein thrombosis — case report and review of the literature

Abstract: Endometriosis is a medical condition in women wherein endometrial cells deposited in the area outside the uterine cavity are influenced by hormonal changes, and produce symptoms depending on the site of implantation. A unique case of retroperitoneal endometriosis causing deep vein thrombosis from extrinsic compression of the right iliac vein is described. Clinical presentation with cyclical leg swelling, coincidental with menstruation and culminating with deep vein thrombosis, although very suggestive, has not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…The case of Rosengarten et al [4] was the first description of DVT due to endometriosis encircling the right external iliac vein. In the case described by Sharma et al [5], the disease had a retroperitoneal localization and DVT of the right common femoral vein, external iliac and distal internal iliac veins occurred. These three patients had no previous history of a DVT and presented the typical cyclic symptomatology of endometriosis, but no previous general symptoms such as episodes of abdominal and pelvic pain, menorrhagia, metrorrhagia, dyspareunia, and dysmenorrhea.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The case of Rosengarten et al [4] was the first description of DVT due to endometriosis encircling the right external iliac vein. In the case described by Sharma et al [5], the disease had a retroperitoneal localization and DVT of the right common femoral vein, external iliac and distal internal iliac veins occurred. These three patients had no previous history of a DVT and presented the typical cyclic symptomatology of endometriosis, but no previous general symptoms such as episodes of abdominal and pelvic pain, menorrhagia, metrorrhagia, dyspareunia, and dysmenorrhea.…”
Section: Discussionmentioning
confidence: 95%
“…Instead, the described patient developed a sudden symptomatology, different from the cyclic catamenial edema of the other patients. In the case described by Sharma et al [5] the patient did not take any anticoagulation therapy and developed DVT. Notwithstanding Rosengarten et al [4] reported the development of DVT despite administration of appropriate medical therapy, similar to what was observed in this case.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…1012 It is believed that the presence of a femoral hernia allows spillage of endometrial tissue from the pelvis into the groin. Endometriosis in the groin can theoretically cause catamenial pain and mass-related symptoms.…”
Section: Discussionmentioning
confidence: 99%